O Ato De Nomear No Discurso De Ódio Contra A Mulher (PERcursos Linguísticos, 2020)
The act of naming is a process marked by the constitution of otherness, in which the other constitutes our social horizon (MOIRAND, 2004; SIBLOT, 1998, 2007). The words selected to name the other are loaded with positions, appraisals and / or ideologies. When referring to our other by nomination, we say more about ourselves, as there is a position taken by the nominator, a definition of himself and the other becomes an image or object of the discourse to be referred to. Considering like that other, the woman victimized by violence due to the fact of being a woman, we aim to analyze the nomination of the feminized body in the context of domestic and family violence against women until the culmination of feminicide, whose aggressions are carried over hate speech. Our question is, therefore, how is the woman named in the hate speech by the perpetrator of the aggression in the context of domestic and family violence against women until the climax of feminicide? Our study is inserted in the dialogical theory of language with conceptual bases in dialogism, in the principle of alterity, in the positioning, in the point of view and in the appreciation within the conception of the nomination and hate speech, which prevails in the context of violence, against the victim’s resistance.